Polypyrrole-Modified Nylon 6 Nanofibers as Adsorbent for the Extraction of Two β-Lactam Antibiotics in Water Followed by Determination with Capillary Electrophoresis - Li, Xinghua (Molecules, 2019)
A solid phase membrane adsorbent—a nylon 6 nanofibers membrane coated by polypyrrole (PPy-PA6-NFsM)—was firstly synthesized and used for extraction of two β-lactam antibiotics (oxacillin and cloxacillin) in urban river water. Then the analytes were detected by capillary electrophoresis with a diode array detector (CE-DAD). The synthesized nanofibers membrane was characterized by scanning electron microscopy and a Fourier transform infrared spectrometer. The experimental conditions were optimized, including the amount used of PPy-PA6-NFsM, pH of the sample solutions, adsorption volume, and desorption conditions. Under the optimal extraction and separation conditions, the detection limits were found to be 2.0 ng/mL for both oxacillin and cloxacillin. The proposed method was applied to the determination of the two β-lactams in water samples of an urban river. The recoveries of these two β-lactams were found to be in the range 84.2–96.4%, demonstrating that PPy-PA6-NFsM has a high extraction capability for these two antibiotics. The relative standard deviations, ranging from 2.26% to 5.29% for intraday measurements and from 2.38% to 7.02% for inter-day determinations, were derived respectively.